1990
DOI: 10.1159/000261245
|View full text |Cite
|
Sign up to set email alerts
|

A Possible Mechanism of Acquired Acid Resistance of Human Dental Enamel by Laser Irradiation

Abstract: A possible mechanism of acquired acid resistance of lased enamel was proposed on the basis of the investigations of optical properties, compositional and structural changes and permeability of lased and unlased human dental enamel. Lased enamel showed a high positive birefringence, suggesting the formation of ‘microspaces’ in enamel. No new products were found, though a decrease of lattice strain and a slight a-axis contraction were recognized in lased enamel compared with unlased enamel. The contents of water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
105
1
18

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(134 citation statements)
references
References 15 publications
10
105
1
18
Order By: Relevance
“…Dentinal permeability might also be reduced as a result of sealing the dentinal tubules up to a considerable depth. [41][42][43] Such alterations in dentinal surfaces might impede the proper bonding of restorative materials and cause cohesive micro-fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Dentinal permeability might also be reduced as a result of sealing the dentinal tubules up to a considerable depth. [41][42][43] Such alterations in dentinal surfaces might impede the proper bonding of restorative materials and cause cohesive micro-fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Acid etching results in chemical changes that may modify the organic matter and decalcify the inorganic component. 14,15 As a result of this demineralization, enamel becomes more susceptible to caries attack, which is induced by plaque accumulation around the bonded orthodontic attachments. Hossain et al 12 reported an increase in the calcium to phosphorus ratio achieved during laser irradiation, which leads to caries inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…3 Additionally, there have been several studies in which it has been observed that enamel structure is modified, increasing the resistance against caries, due to thermally induced chemical and structural changes in the intrinsic mineral and organic matrix, as well as reduction of carbonates. [4][5][6] The aim of this in vitro study was to evaluate and compare shear bond strength of sealants prior to enamel conditioning under several etching protocols in permanent teeth.…”
mentioning
confidence: 99%